Ulceration in Prolidase Deficiency: Successful Treatment with Anticoagulants - Kira Süßmuth; Dieter Metze; Ana-Maria Muresan; Kai Lehmberg; Udo zur Stadt; Carsten Speckmann; Julien Heinrich Park; Thorsten Marquardt; Vinzenz Oji; Tobias Goerge (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)